Polarization and Rationality of Political Choices of the People of Padang City in the 2024 Presidential Election - M. Nursi (Journal Research of Social Science, Economics, and Management, 2024)
The 2024 Presidential Election (Pilpres) in Indonesia, including in West Sumatra and the City of Padang, is a strategic battle, not only in the context of heading towards a Golden Indonesia in 2045 but taking place in a unique configuration and axis of political power and ideology and development ideology, namely between the political ideology of Islamism with Nationalism, and between the development ideology "Change" (01) and the axis of development ideology "Continue" (Jokowisme). Even in the electoral districts of West Sumatra province and Padang City where Jokowi lost badly in the 2014 presidential election with a score of 23.1% vs. 76.9% (Prabowo), and in the 2019 presidential election he lost again absolutely with a vote share of only 14.05% vs. 85.95% (Prabowo), in fact in the 2024 presidential election Pabowo (02) experienced defeat, and was won by the pair Anis-Amin (01) (28.18%), Prabowo-Gibran (02) (16.56%), and Ganjar-Mahfud (1.87%). This research uses a quantitative approach and survey methods, a population of 666,178 and a sample of 5362 spread across 2681 polling stations, with random sampling techniques and questionnaire instruments, and percentage and correlational data analysis techniques assisted by SPSS version 20, so in accordance with the objectives, the findings are that: 1). The political attitudes of rationality are less strong (55.4) and 15.3% are irrational, while those with strong rational potential are 70%, and the not strong rational category is 30%.